2009
DOI: 10.3109/14756360903179401
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of progesterone derivatives as 5α-reductase inhibitors, and their effect on hamster prostate weight

Abstract: In this study, we report the synthesis and biological evaluation of four 6- and 17-substituted progesterone derivatives (7-10). These compounds were prepared from the commercially available 17alpha-acetoxyprogesterone. The biological effect of these steroids was demonstrated in in vivo as well as in vitro experiments. In the in vivo experiments, we measured the activity of 6-10 on the weight of the prostate glands of gonadectomized hamsters treated with testosterone (T). For the studies in vitro, we determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…[77] Similar results were observed with certain derivatives of 16b-methylpregnadiene-3,20-diones, [80] and 3-substituted pregna-4, 16-diene-6 and 20-dione derivatives. [81] In a study by Bartoeff, [79] compounds 6-9 exhibited 50% reduction in 5a-reductase activity; C-6 substituted progesterone derivatives (that did not posses a double bond in ring B) elicited highest inhibitory activity. [79] These results, and the fact that they did not act on androgen receptors, speaks for enzymatic inhibition as the underlying mechanism.…”
Section: Progesterone In Prostate Hypertrophy and Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[77] Similar results were observed with certain derivatives of 16b-methylpregnadiene-3,20-diones, [80] and 3-substituted pregna-4, 16-diene-6 and 20-dione derivatives. [81] In a study by Bartoeff, [79] compounds 6-9 exhibited 50% reduction in 5a-reductase activity; C-6 substituted progesterone derivatives (that did not posses a double bond in ring B) elicited highest inhibitory activity. [79] These results, and the fact that they did not act on androgen receptors, speaks for enzymatic inhibition as the underlying mechanism.…”
Section: Progesterone In Prostate Hypertrophy and Prostate Cancermentioning
confidence: 99%
“…Several progesterone derivatives were analysed further, in various studies, in regard to their 5 α ‐reductase activity and role in prostate hypertrophy and cancer; [76–78] some compounds inhibited growth of cell lines of both prostate cancer and lymphocytes, without any toxic effects in vivo [76] . In studies comparing some progesterone derivatives of 17 α ‐acetoxyprogesterone [77,79] with testosterone in gonadectomized male hamsters, significant decrease in prostrate weight was observed in the progesterone‐derivative group, [77,79] as compared with testosterone‐treated hamsters, and enzymatic activity was reduced [80] by 50% [77] . Similar results were observed with certain derivatives of 16 β ‐methylpregnadiene‐3,20‐diones, [80] and 3‐substituted pregna‐4, 16‐diene‐6 and 20‐dione derivatives [81] .…”
Section: Novel Actions Of Progesteronementioning
confidence: 99%
“…Alternatively, these suggested endocrine interactions might be additionally influenced by an altered 5 ␣ -reductase metabolism, as has been indicated by previous experiments using inhibiting substances [26][27][28] . In a hamster model, in which the effects of progestin derivatives on prostate size were examined, it was suggested that these substances may act as 5 ␣ -reductase inhibitors and thereby avoid dihydrotestosterone-driven prostate growth increase, also interacting with the AR [29,30] . Unexpectedly, after the treatment change of groups with NETE, no significant prostate growth was measured in animals of group I.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of the pigmented spot in male hamsters depends on the DHT level and also on the conversion of T to DHT catalyzed by 5α-R. The high in vitro activity of compounds 33 and 34 could be explained by the presence of the α,β-unsaturated carbonyl function, which imparts a higher electrophilic character and thus forms a tight complex with the nucleophilic part of the amino acid; as a result, enhanced biological activity of these compounds was observed [92-93]. …”
Section: Recent Advances In New Steroidal and Non-steroidal Inhibitormentioning
confidence: 99%
“…( 17 ) showed a very low binding affinity for the AR; nevertheless, in the in vivo experiments they decreased the weight of prostate and seminal vesicles of gonadectomized and T-treated hamsters, suggesting that these compounds could function as prodrugs [93]. …”
Section: Recent Advances In New Steroidal and Non-steroidal Inhibitormentioning
confidence: 99%